2020
DOI: 10.3329/bjb.v49i1.49121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vermicompost and PK on growth and protein content of spinach (Spinacia oleracia L.)

Abstract: Results of a pot experiment carried out on spinach with vermicompost (5, 10 and 15 ton/ha), phospho-rous (10, 20 and 30 kg/ha) and potassium (20, 30 and 40 kg/ha) fertilizers showed that plant height, leaf area, fresh and dry weight of plants increased significantly (p ≤ 0.5) over the control. Highest height (23.55 cm), leaf area (80.88 cm2/plant), fresh weight (3.838 g/plant) and dry weight (0.274 g/plant) were maximum in VC15P20K30, VC15P30K30, VC10P20K30 and VC10P10K40, respectively, while leaf number was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
1
5
0
2
Order By: Relevance
“…Immediately after harvest, the fresh weight of leaf, stem, and root was recorded. Samples were air-dried at room temperature for three days and finally oven-dried at 65°C for 72 hours (Islam et al 2020). Dry weight was recorded, ground in a mechanical grinder, and stored in air-tight plastic bottles for chemical analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately after harvest, the fresh weight of leaf, stem, and root was recorded. Samples were air-dried at room temperature for three days and finally oven-dried at 65°C for 72 hours (Islam et al 2020). Dry weight was recorded, ground in a mechanical grinder, and stored in air-tight plastic bottles for chemical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The highest protein content was found in the leaf and the lowest was recorded in the root. Islam et al (2020) reported that the highest protein content in leaf (24.65%) was achieved in VC 15 ton/ha, P 10 kg/ha, K 20 kg/ha in Spinacia oleracea. Magomya et al (2014) collected ten different plants samples from the wild and farmland of Nigeria and found that protein range from 2.63 to 18.59%.…”
Section: Concentrations Of N P K and S In Leaf Stem And Rootmentioning
confidence: 99%
“…Hibiscus canabinus, Haematostaphis barteri, Sesamum indicum, Balanites aegyptiaca, Cassia tora, Celtisin tegrifolia, Anonas En galensiss, Ceiba pentandra, Ficus ingens and Solanum melongena the protein of which ranged from 2.63-18.59%. Islam et al (2020) reported that the highest protein content (24.61%) was obtained in spinach in the treatment VC 15 ton ha-1 P 10kgha-1 K 20kgha-1 .…”
Section: Protein Content In Fruitsmentioning
confidence: 97%
“…Sin embargo, considerando los promedios, con el bocashi se obtuvo la mayor área foliar incluso superando a la fertilización química. Los valores medidos fueron incluso mayores a los reportados por Islam et al (2020), quienes llevaron a cabo un experimento fertilizando un cultivo de espinaca con vermicomposta (5, 10 y 15 ton / ha), fósforo (10, 20 y 30 kg / ha) y potasio (20, 30 y 40 kg / ha) y reportaron una área foliar máxima de 80,88 cm 2 / planta.…”
Section: Mediciones a La Espinacaunclassified
“…Este efecto benéfico de los fertilizantes orgánicos se ha reportado por otros autores, por ejemplo, Ievinsh (2011) indica que la vermicomposta contiene sustancias biológicamente activas producidas a través de la interacción entre los microorganismos y las lombrices, algunos de estos metabolitos son similares a las hormonas vegetales. Además, puede actuar como acondicionador del suelo y fertilizante orgánico, ya que mejora disponibilidad de nutrientes minerales, aumenta la aireación y mejora el ciclo de nutrientes y del agua (Islam et al, 2020). Estudios proporcionaron evidencia de que la composta afecta positivamente la calidad del suelo en términos de actividades biológicas y actividades deshidrogenasa, fosfatasa y glucosidasa especialmente, debido principalmente a una mayor disponibilidad de carbono (Bonanomi et al, 2014).…”
Section: Mediciones a La Espinacaunclassified